Probiotic properties of Bifidobacterium species isolated from mother’s milk and infant feces (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
Probiotics are live microorganisms that provide health benefits when consumed. Bifidobacteria are one of the major genera of bacteria that make up the colon flora in mammals and have great beneficial impact on health. This study was performed to culture and characterize some potential Bifidobacterium sp. isolated from mother's milk and infant feces. Eleven isolates were presumptively identified as Bifidobacteriums sp. based on morphological characteristic and biochemical properties such as catalase, oxidase, Esculin test, Gelatinase activities and production of gas from glucose. Probiotic potentials of the isolates were investigated through probiotic potentiality tests e.g. pH tolerance test, NaCl tolerance test, bile salt tolerance test, antimicrobial activity, growth rate in gastric juice, antimicrobial susceptibility (Antibiogram). Four of the isolates BI-3, BI-5, BI-9, and BI-14 were observed as potential probiotic based on their probiotic activities. These isolates showed resistance to stomach pH (pH 3.0), tolerance against 0.3% bile concentration and gastric juice tolerance. Most of the isolates were able to grow at 1- 6% NaCl concentration and the growth declined with the increase of the salt concentration. Proteolytic activity was measured to estimate the probable role of probiotics in protein digestion. For this purpose milk protein digestion was tested and these isolates had showed better proteolytic activity than others. Antimicrobial activity against pathogens showed better probiotic properties. These isolates were found to have moderately antibiotic susceptible to common antibiotics. This experiment revealed that these four isolates BI-3, BI-5, BI-9, and BI-14 have good probiotic properties and can be used as probiotics after successful molecular identification and completion of animal trial.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 122-135